Efektivitas Program “KPU Goes to Campus” dalam Upaya Meningkatkan Partisipasi Pemilih di Provinsi Jawa Timur - Soraya, Amanda; Nawangsari, Ertien Rining (IAI Nasional Laa Roiba Bogor, 2025)
KPU Goes to Campus is one of the innovative breakthrough programs carried out by the General Election Commission (KPU). This program is carried out based on KPU Regulation No. 9 of 2022 concerning community participation as a strategy in integrating political education for students which aims to provide insight into general elections (elections), voting rights and to increase the participation of young voters in elections, especially in regional head elections (pilkada). The East Java Provincial KPU, as one of the most important pillars, is the key to the success of the 2024 simultaneous regional elections. Therefore, this study aims to determine the effectiveness of the program carried out by the East Java Provincial KPU, which has a fixed number of voters of 31,280,418 people, including 73,001 new voters. Based on the results of the research, it shows that this program has succeeded in increasing students' awareness and political participation through education about voting rights, the election process, and their responsibilities as voters. The indicators used show that this program is very effective in an effort to increase voter participation by increasing voter participation from 67.39% in the 2018 regional elections to 70.06% in the 2024 regional elections in East Java. This program has a real impact on the mindset of students as a young generation who actively contribute to the democratic process.